Digestion method of polycrystalline silicon

By oxidizing polysilicon at high temperature and then using HF to digest SiO2, and performing silicon volatilization and acid removal treatments, the problem of incomplete polysilicon digestion and large error in test results is solved, and fast and accurate impurity detection is achieved.

CN119309879APending Publication Date: 2025-01-14ANYANG INST OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411406952.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing polysilicon digestion methods have problems such as incomplete digestion, cumbersome procedures, low efficiency and large systematic errors in the test results.

Method used

After using high-temperature oxidation of polysilicon, HF is used to digest SiO2, and the residual silicon and HF in the matrix are reduced through silicon volatilization and acid removal steps, thereby reducing the corrosion of the test instrument and the impact on the test results.

Benefits of technology

The rapid and complete digestion of polysilicon is achieved, the digestion time is shortened, the system error is reduced, and the accuracy of impurity detection is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119309879A_ABST
    Figure CN119309879A_ABST
Patent Text Reader

Abstract

The invention discloses a digestion method of polycrystalline silicon. The digestion method comprises the following steps: S1, crushing a to-be-detected standard sample: crushing the to-be-detected standard sample of the polycrystalline silicon into polycrystalline silicon powder with a certain particle size; s2, polycrystalline silicon oxidation: oxidizing the polycrystalline silicon powder into silicon dioxide powder at high temperature; s3, digestion, silicon volatilization and acid removal: pouring a certain amount of silicon dioxide powder into a capped polytetrafluoroethylene digestion tank, adding a certain amount of pure water and hydrofluoric acid, heating and digesting after capping, and then uncapping, silicon volatilization, acid removal and concentration to be nearly dry; and S4, adding dilute nitric acid into the digestion tank to dissolve substances in the tank, transferring the dissolved solution into a plastic volumetric flask, washing the digestion tank with pure water, merging washing solutions, transferring the combined washing solutions into the plastic volumetric flask, diluting the liquid in the volumetric flask to a scale with pure water, uniformly mixing, standing, taking supernate, and filtering to obtain the digestion solution to be detected. The digestion method disclosed by the invention is short in digestion time, the consumption of nitric acid is reduced, and the boron impurity in the polycrystalline silicon is more accurately detected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polysilicon digestion method, which is used for testing the impurity content in the polysilicon and belongs to the technical field of semiconductor material characterization testing. Background Art

[0002] Polysilicon is widely used in electronics, photovoltaics, metallurgy and other industries. Its electrical and mechanical properties are closely related to its impurity content. Therefore, testing the impurity content of polysilicon is very important for the production and application of polysilicon, especially in the photovoltaic industry. When using crystalline silicon to prepare solar cells, the purity of solar silicon must be greater than 6N (99.9999%), otherwise the photoelectric conversion efficiency and service life of the solar cell will be seriously reduced.

[0003] At present, in production and laboratories, the main testing methods for the impurity content of polysilicon include inductively coupled plasma atomic emission spectrometry (ICP-OES) and inductively coupled plasma mass spectrometry (ICP-MS). Using these methods, the polysilicon sample to be tested (standard sample to be tested) must first be digested from solid to liquid before its impurity content can be tested.

[0004] In 2016, Yang Jie et al. used hydrofluoric acid and nitric acid to digest polysilicon in a polytetrafluoroethylene digestion tank with the assistance of a 200W ultrasonic generator. Take the standard sample to be tested - 0.25g of silicon powder, particle size 70~420mm; V(HNO 3 )=1.0mL, purity 70%; V(HF)=2.8mL, purity 49%; V(H 2 O) = 2.0mL, resistivity> 18MΩ·cm; some mannitol of high purity. After 2 days, the polysilicon was completely digested.

[0005] In 2012, patent CN101685048 B published "A method and device for detecting the purity of polysilicon". The reagent used to digest polysilicon is: HNO 3 and HF, Teflon container material, heating temperature 110-120℃. Using HNO 3 +HF digestion of polysilicon is a common method in the industry. This method requires "driving away the acid" and "volatilizing the silicon" to digest polysilicon, otherwise it will have a serious impact on the test instrument and test results. This method takes a long time to digest silicon, and the reaction speed is slow, 2-3 days, the reaction is not thorough, the test results have large systematic errors, and the silicon solution is not easy to be clear and transparent, and needs to be filtered.

[0006] To dissolve silicon with hydrofluoric acid, holes are required, that is, H 2 O 2If the holes are exhausted, the digestion will stop, so an oxidizing acid such as nitric acid is needed. Digestion of polysilicon is a difficult task and is a necessary step for testing the impurity content of polysilicon using ICP-OES and ICP-MS.

[0007] There are two traditional methods for digesting polysilicon: alkaline digestion and acid digestion.

[0008] ①The principle of alkaline digestion method is: Si+2NaOH+H 2 O→Na 2 SiO 3 +2H 2 ↑ The advantages of this method are: fast reaction speed, low reaction temperature, and simple equipment required; the disadvantages are: "matrix silicon" cannot be eliminated, the solution concentration is high, and when testing impurities, the digestion solution (silicon solution) can easily block the matrix tube of the test instrument. The matrix silicon spectrum has an overlapping phenomenon with the spectrum of the element to be tested, and the test results need to be corrected.

[0009] ②The principle of acid digestion method is: 3Si+18HF+4HNO 3 →3H 2 SiF 6 +4NO↑+8H 2 O The advantages of this method are: the required equipment is simple and the reaction temperature is low; the disadvantages are: the digestion speed of the sample to be tested is slow, the digestion of the sample to be tested is incomplete, HF has a corrosive effect on the "quartz matrix tube" of the test instrument ICP-OES, and it is necessary to "drive away the acid" and "volatilize the silicon", and the digestion process is complicated. If the concentration of nitric acid is too high, a large amount of reaction heat will be generated, causing the formed fluoroboric acid HBF 4 Decomposed into volatile boron trifluoride, causing serious loss of boron element, resulting in seriously low B element test results: B+3HNO 3 (concentrated) → H 3 BO 3 +3NO 2 ↑ 4HF+H 3 BO 3 →HBF 4 +3H 2 O HBF 4 →HF↑+BF 3 ↑ Therefore, when selecting a digestion agent, it is necessary to consider: whether the standard sample to be tested can be quickly and completely digested; whether the element to be tested will evaporate or be lost; whether the element to be tested will generate insoluble precipitates with other components to be tested; whether the spectrum of the element to be tested and the matrix will interfere with each other; whether the digestion agent will damage the container or instrument, etc. Summary of the invention

[0010] In view of the problems existing in the prior art, the present invention provides a method for digesting polysilicon, aiming to solve at least one of the many problems such as incomplete digestion of polysilicon, complicated digestion procedure, low efficiency, large systematic error in test results, and complex technical requirements.

[0011] The core technologies of polysilicon digestion are as follows: ① polysilicon digestion, converting solid into liquid; ② silicon volatilization, volatilizing matrix silicon; ③ acid removal, volatilizing the remaining HF in the digestion solution to avoid corrosion of the glass tube of the test instrument.

[0012] The technical solution of the present invention is as follows: A method for digesting polycrystalline silicon comprises the following steps: S1. Grinding the standard sample to be tested: Grinding the polysilicon standard sample to be tested into polysilicon powder of a certain particle size; S2, polysilicon oxidation: oxidize polysilicon powder into silicon dioxide powder at high temperature; S3. Digestion, volatilization of silicon and removal of acid: Take a certain amount of silicon dioxide powder, pour it into a covered polytetrafluoroethylene digestion tank, add a certain amount of pure water and hydrofluoric acid, cover it and heat it to 110-120℃, digest it, then remove the cover, volatilize silicon, remove acid and concentrate it to nearly dryness.

[0013] S4. Add dilute nitric acid to the digestion tank to dissolve the residual substances in the tank, transfer the dissolved liquid into a plastic volumetric bottle, and then wash the digestion tank with pure water. The washing liquid is also combined and transferred into a plastic volumetric bottle. Dilute the liquid in the volumetric bottle with pure water to the scale, mix well, let it stand, take the supernatant, filter, and obtain the digestion solution to be tested.

[0014] Furthermore, the particle size of the polysilicon powder after crushing in S1 is 84-342 μm.

[0015] Furthermore, the oxidation temperature of the polysilicon in S2 is 900°C.

[0016] Furthermore, a certain amount of propylene glycol may be added to the digestion tank during the digestion in S3.

[0017] Furthermore, a certain amount of perchloric acid may be added when dissolving the material in the tank in S4.

[0018] A method for testing the impurity content in polysilicon comprises the following steps: crushing a polysilicon standard sample to be tested into polysilicon powder of a certain particle size, taking a certain amount of the polysilicon powder for thermogravimetric analysis, obtaining the conversion relationship between the mass of silicon dioxide obtained after heating and the mass of polysilicon before heating from the thermogravimetric analysis diagram, then using the aforementioned polysilicon digestion method to obtain a digestion solution, using inductively coupled plasma atomic emission spectrometry to test, and finally calculating the content of various impurities according to a certain formula.

[0019] Beneficial effect: The invention has the advantages of first oxidizing the polysilicon sample into silicon dioxide at high temperature, and then using HF to digest SiO 2 Instead of using the traditional hydrofluoric acid and nitric acid to directly oxidize and digest polysilicon, SiO2 reacts quickly with HF, the digestion time is short, and the reaction temperature is low; the amount of nitric acid used is reduced, nitrogen oxide emissions are low, and it is environmentally friendly; finally, by controlling the digestion temperature and adding propylene glycol, the loss of impurity boron elements is small, and the detection of boron impurities in polysilicon is more accurate. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the TG-DSC thermogravimetric analysis diagram of polycrystalline silicon in air. DETAILED DESCRIPTION

[0021] The present invention is further described below with reference to specific cases.

[0022] A method for digesting polycrystalline silicon comprises the following steps: S1. Crushing the standard sample to be tested. Crushing the standard sample to be tested (polysilicon powder) into 84-342mm, or even smaller particle size.

[0023] S2, polysilicon oxidation. At a high temperature of 900°C, polysilicon powder is oxidized to SiO 2 powder,

[0024] S3, polysilicon digestion, silicon volatilization and acid removal. Take about 0.25g (<0.5g) of the above silicon dioxide, pour it into a covered polytetrafluoroethylene digestion tank, add V(HF) = 3mL, purity 49% (mass fraction); ... 2 O) = 2.0 mL, resistivity > 18 MΩ·cm, after 10 min, the silicon dioxide is completely dissolved. 2 It is hydrophilic and will not float on the liquid surface during the digestion process. 2 In HF solution, the digestion speed is fast and it can be completely dissolved and converted from solid to liquid.

[0025]

[0026] Heating to 110-120℃ is to accelerate the volatilization rate of matrix silicon and HF. Cover and digest the "concentrated solution" until it is almost dry, then remove the cover to volatilize silicon and drive away acid, reduce the influence of matrix silicon on the test results, and reduce the corrosion of hydrofluoric acid on the quartz parts of the test instrument. If the digestion temperature is too low, the elements to be tested cannot be extracted well, affecting the recovery rate of the spiked elements to be tested; if the temperature is too high, it is easy to cause serious loss of boron and other elements to be tested. In order to improve work efficiency, the maximum temperature of "volatilizing silicon", "driving away acid" and digestion shall not exceed 140℃.

[0027] If there is residue on the inner wall and bottom of the digestion tank, continue to add 0.5mL perchloric acid, 2mL dilute nitric acid and high-purity water to dissolve the soluble residue with warm water, and wash the digestion tank at the same time. Transfer the washing liquid into a 100mL plastic volumetric bottle, dilute to the scale with high-purity water, and mix well. Let it stand for 0.5h, take the supernatant, filter it and test it.

[0028] During the digestion process of polysilicon, since the digestion tank is sealed in a high-pressure sealed environment, serious volatilization loss of the elements to be measured will not occur.

[0029] In step S3, glycerol is added, V(C 3 H 8 O 3 )=0.5mL, concentration 0.25%, B+2CH 2 OH-CHOH-CH 2 OH→[CH 2 O-CHOH-CH 2 OB-CH 2 O-CHOH-CH 2 O] - +4H + Glycerol has the function of complexing the element boron (B), which can make trace amounts of B less likely to volatilize during the heating process and improve the test accuracy.

[0030] Oxidation of polysilicon. Figure 1 This is the thermogravimetric analysis of polysilicon powder in air. The DSC curve shows that from room temperature to 400°C, it is an endothermic process. Polysilicon gradually loses moisture and absorbs heat during the heating process. At the same time, it reacts with O in the air. 2 Reaction to generate SiO 2 , exothermic, the weight of polysilicon powder gradually increases (TG curve), the overall effect, the heat absorption is greater than the heat release, indicating that SiO 2 The output is small. From 400℃ to 890℃, it is an exothermic process. Silicon powder continues to react with O 2 Reaction to generate SiO 2From 780℃ to 890℃, the heat release rate of silicon powder gradually decreases, indicating that the oxidation of silicon powder is gradually complete.

[0031] Si+O 2 →SiO 2 +Q From room temperature to 890℃, the duration is 89min, and the weight of silicon powder increases by 17.8%.

[0032] SiO 2 Conversion relationship of original polysilicon content in powder: 1g polysilicon is contained in 1.178g silicon dioxide.

[0033] , where m Si is the mass of Si, in g; m SiO2 SiO 2 The mass of is in g.

[0034] The benefits of the present invention are: using HF to digest SiO 2 ; Using oxygen to oxidize polysilicon instead of oxidizing acid to oxidize polysilicon, the polysilicon is fully oxidized, which is environmentally friendly and can completely convert polysilicon into SiO 2 , SiO 2 The reaction with HF is rapid and thorough in a short time; polysilicon is digested in a closed high-pressure environment, and the loss of the elements to be measured is small.

[0035] Case 1: In an agate crucible, the polysilicon powder is ground to 84-342 mm, or even smaller.

[0036] In a rotary resistance furnace, under an oxygen environment, the sample to be tested is heated to 900°C at a heating rate of 5°C / min for 3 hours, then kept at this temperature for 2 hours, and then cooled naturally. When the temperature drops to room temperature, it is taken out. The polysilicon powder is completely converted into silicon dioxide powder.

[0037] Take the above SiO 2 0.1324g of powder, converted to 0.1124g of silicon powder, is poured into a sealed polytetrafluoroethylene digestion tank, and 2mL of high-purity water is added. Stir evenly, and then 2.8mL of 49% reagent-grade hydrofluoric acid is added. On an intelligent magnetic stirrer, the magnetic stirring rate is 600r / min, the stirring time is 0.5h, and the heating temperature is 120°C. Uncover the "silicon evaporation" and "acid removal" and continue to heat the concentrated solution until it is nearly dry. Then add 2mL of dilute nitric acid to wash the wall and bottom of the digestion tank. The washing liquid is transferred to a 25mL plastic container bottle, and then 2mL of high-purity water is added to wash the wall and bottom of the digestion tank. The washing liquid is transferred to the same plastic container bottle, diluted to the scale with high-purity water, and mixed. Let it stand for 0.5h, take the supernatant, filter, and test.

[0038]

[0039] Where, ω is the impurity concentration of the standard sample to be tested, in ppmw; c SiO2标样 is the reading of the standard instrument, in mg / L; c 空白 is the blank sample instrument reading, in mg / L; m Si标样 is the mass of the standard sample to be tested, in g; V 浸取液 , unit is mL. The ICP-OES test results are shown in Table 1.

[0040] Table 1 Polysilicon impurity test

[0041] Test Elements The mass of Si standard sample to be tested (g) Leaching solution volume (mL) Instrument reading (mg / L) Blank sample reading (mg / L) Sample concentration (ppmw) B 0.1124 25 0.0013 0.0001 0.2669 Cu 0.1124 25 0.0071 0.0001 1.5569 Fe 0.1124 25 0.0769 0.0001 17.0819 Ga 0.1124 25 0.0023 0.0001 0.4893 P 0.1124 25 0.0010 0.0001 0.2002 Zn 0.1124 25 0.0314 0.0001 6.9617 Take SiO 2 0.0992g of powder, converted to 0.0842g of silicon powder, was poured into a sealed polytetrafluoroethylene digestion tank, 2mL of high-purity water was added, stirred evenly, and then 2.6mL of 49% reagent-grade hydrofluoric acid was added, followed by laboratory-grade V(C 3 H 8 O 3 )=0.5mL, concentration 0.25%, closed. On the intelligent magnetic stirrer, the magnetic stirring rate is 500r / min, the stirring time is 0.5h, and the heating temperature is 110°C. Uncover the "silicon evaporation" and "acid removal", continue to heat the concentrate until it is almost dry, then add 3mL of high-purity water, 3mL of dilute nitric acid and 0.5mL of perchloric acid, wash the walls and bottom of the digestion tank, after 10 minutes, transfer the washing liquid to a 25mL plastic container bottle, add 3mL of high-purity water to wash the walls and bottom of the digestion tank, transfer the washing liquid to the same plastic container bottle, dilute to the scale with high-purity water, and mix well. Let stand for 0.5h, take the supernatant, filter, and test. The ICP-OES test and calculation results are shown in Table 2.

[0042] Table 2 Polysilicon impurity test Test Elements The mass of Si standard sample to be tested (g) Leaching solution volume (mL) Instrument reading (mg / L) Blank sample reading (mg / L) Sample concentration (ppmw) B 0.0842 25 0.0010 0.0001 0.2672 Cu 0.0842 25 0.0045 0.0001 1.3064 Fe 0.0842 25 0.1807 0.0001 53.6223 Ga 0.0842 25 0.0023 0.0001 0.6532 P 0.0842 25 0.0005 0.0001 0.1188 Zn 0.0842 25 0.0226 0.0001 6.6805 .

[0043] This method can also be used for SiO 2 Impurity content test.

Claims

1. A method for digesting polycrystalline silicon, characterized in that: The following steps are involved: S1. Grinding the standard sample to be tested: Grinding the polysilicon standard sample to be tested into polysilicon powder of a certain particle size; S2, polysilicon oxidation: oxidize polysilicon powder into silicon dioxide powder at high temperature; S3, digestion, silicon volatilization and acid removal: take a certain amount of silicon dioxide powder, pour it into a covered polytetrafluoroethylene digestion tank, add a certain amount of pure water and hydrofluoric acid, cover it and heat it to 110-120℃, digest it, then remove the cover, evaporate the silicon, remove the acid, and concentrate it to nearly dryness; S4. Add dilute nitric acid to the digestion tank to dissolve the residual substances in the tank, transfer the dissolved liquid into a plastic volumetric bottle, and then wash the digestion tank with pure water. The washing liquid is also combined and transferred into a plastic volumetric bottle. Dilute the liquid in the volumetric bottle with pure water to the scale, mix well, let it stand, take the supernatant, filter, and obtain the digestion solution to be tested.

2. A method for digesting polycrystalline silicon according to claim 1, characterized in that: The particle size of the polysilicon powder after crushing in S1 is 84-342 μm.

3. A method for digesting polycrystalline silicon according to claim 1, characterized in that: The oxidation temperature of polysilicon in S2 is 900°C.

4. The method for digesting polycrystalline silicon according to claim 1, characterized in that: During digestion in S3, a certain amount of propylene glycol may also be added to the digestion tank.

5. The method for decomposing polycrystalline silicon according to claim 1, characterized in that: A certain amount of perchloric acid can also be added when dissolving the contents of the tank in S4.

6. The method for decomposing polycrystalline silicon according to claim 1, characterized in that: The content of original polysilicon in a certain amount of silicon dioxide powder in S3 is calculated as follows: Si =m SiO2 / 1.178.

Citation Information

Patent Citations

  • Purity detecting method and device for polysilicon

    CN101685048B